Reduction of N-Acetylglucosaminyltransferase-I Activity Promotes Neuroblastoma Invasiveness and EGF-Stimulated Proliferation In Vitro - Adam P. Burch; M. Kristen Hall; Debra Wease; Ruth A. Schwalbe (International Journal of Translational Medicine)
Aberrant N-glycosylation has been associated with progression of the pediatric cancer neuroblastoma (NB) but remains understudied. Here we investigated oligomannose N-glycans in NB by genetic editing of MGAT1 in a human NB cell line, BE(2)-C, called BE(2)-C(MGAT1−/−). Lectin binding studies confirmed that BE(2)-C(MGAT1−/−) had decreased complex and increased oligomannose N-glycans. The relevance of 2D and 3D cell cultures was demonstrated for cell morphology, cell proliferation, and cell invasion, thereby highlighting the necessity for 3D cell culture in investigating cancerous properties. Western blotting revealed that oligomannosylated EGFR had increased autophosphorylation. Proliferation was decreased in BE(2)-C(MGAT1−/−) using 2D and 3D cultures, but both cell lines had similar proliferation rates using 3D cultures without serum. Upon EGF treatment, BE(2)-C(MGAT1−/−), but not BE(2)-C, showed increased proliferation, and furthermore, the mutant proliferated much faster than BE(2)-C under 3D conditions. Cell spheroid invasiveness was greatly increased in BE(2)-C(MGAT1−/−) compared with BE(2)-C. Moreover, invasiveness was reduced in both cell lines with either EGF or RhoA activator treatment, regardless of the N-glycan population. Thus, this study further extends our earlier findings that oligomannose N-glycans enhance NB cell invasiveness, and that EGF stimulation of oligomannosylated EGFR greatly enhances cell proliferation rates, underlining the role of oligomannose N-glycans in the promotion of NB.